Method for preparing cement-free concrete by using biomimetic polymer

By using bionic polymers as cementitious agents, industrial waste and construction waste are cemented together to prepare cementless concrete, solving the problems of high energy consumption and high carbon emissions in the existing technology, and achieving low carbon environmental protection and excellent building performance.

CN119774920APending Publication Date: 2025-04-08SOUTHEAST UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510014850.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art still relies on cement as cement when preparing concrete using industrial waste and construction waste, resulting in high energy consumption and high carbon emissions.

Method used

Bionic polymers are used as cementitious agents to cement industrial waste and construction waste particles of different particle size ranges together to prepare cementless concrete. Specific steps include preparing raw materials, stirring evenly, forming concrete slurry, adding fine aggregates and coarse aggregates, loading them into molds for curing and demolding.

Benefits of technology

It has achieved concrete materials without cement and carbon emissions, reduced carbon emissions in the cement production process, and has low carbon and environmental protection, excellent anti-aging performance, good waterproof performance and recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing cement-free concrete by using a biomimetic polymer. The cement-free concrete is prepared from the following raw materials in parts by weight: 290-450 parts of solid waste powder, 680-810 parts of solid waste fine aggregate, 980-1200 parts of solid waste coarse aggregate and 160-280 parts of biomimetic polymer emulsion. The biomimetic polymer is adopted as a cementing agent, industrial waste particles and building waste particles with different particle sizes are cemented together, a cement-free and carbon-emission-free concrete material with the strength equivalent to that of common concrete is formed, the building waste can be effectively utilized, the use amount of natural aggregate can be reduced, and carbon emission is reduced. Meanwhile, through reasonable design, the problem of waste accumulation can be effectively solved, and cyclic utilization of resources and sustainable development of the environment are achieved. The cement-free concrete prepared from the biomimetic polymer has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for preparing cement-free concrete by utilizing bionic polymers. Background Art

[0002] With the rapid development of industrialization and urbanization, the output of industrial waste and construction waste has increased dramatically, bringing great pressure to the environment. According to statistics, every new 10,000 square meters of building will generate 500 to 600 tons of construction waste, while the demolition of 10,000 square meters of old buildings will generate 6,000 to 15,000 tons of construction waste. At the same time, industrial waste such as fly ash, steel slag, blast furnace slag, etc. are also piled up in large quantities and difficult to consume effectively. These wastes not only occupy a large amount of land resources, but may also cause long-term pollution to the environment and ecosystem. In addition, the cement production process requires calcination at about 1450°C. Cement consumes a lot of energy (3.3GJ of heat energy per ton of cement) and a lot of carbon emissions (800 kg of carbon dioxide per ton of cement), which brings great pressure to the ecosystem.

[0003] At present, cement is still mostly used as a binder for preparing cement concrete from industrial solid waste and construction waste, which cannot solve the high energy consumption and high carbon emissions generated in the cement production process. Biological systems can provide rich inspiration for improving building materials. For example, sandcastle worms can bind sand or shell fragments together through their inherent secretion of adhesives to form a solid group sandcastle. Using biomimetic polymers as binders to bind industrial waste and construction waste particles of different particle sizes together to form cement-free and carbon-free concrete materials has great application prospects. Summary of the invention

[0004] To solve the above problems, the present invention discloses a method for preparing cement-free concrete using bionic polymers. Industrial waste and construction waste particles of different particle size ranges are bonded together by preparing bionic polymers to form a cement-free and carbon-free concrete material with a certain strength.

[0005] To achieve the above object, the technical solution of the present invention is as follows: A method for preparing cement-free concrete using biomimetic polymers comprises the following steps: First, prepare the raw materials: 290-450 parts of solid waste powder, 680-810 parts of solid waste fine aggregate, 980-1200 parts of solid waste coarse aggregate, and 160-280 parts of bionic polymer emulsion; The weighed solid waste powder is stirred with the biomimetic polymer emulsion to make the materials evenly mixed to form a concrete slurry, and then the solid waste fine aggregate and solid waste coarse aggregate are added and stirred evenly, and the slurry is put into a mold for curing. After curing and demoulding, a cement-free concrete product is formed; Furthermore, solid waste powder is obtained by grinding and screening industrial waste and construction waste, such as concrete blocks, bricks, waste sand, fly ash, steel slag, blast furnace slag and other powders, with a particle size range of 7-200 microns.

[0006] Furthermore, solid waste fine aggregates are obtained by crushing and screening industrial waste and construction waste, such as concrete blocks, bricks and stones, waste sand, steel slag, blast furnace slag and other fine aggregates, with a particle size range of 0.1-5 mm.

[0007] Furthermore, the coarse aggregate of solid waste is obtained by crushing and screening industrial waste and construction waste, such as concrete blocks, bricks and stones, waste sand, steel slag, blast furnace slag and other coarse aggregates, with a particle size range of 5-60 mm.

[0008] Furthermore, the biomimetic polymer emulsion is a high-bonding biomimetic polymer prepared from quaternary ammonium chitosan and sodium alginate. The quaternary ammonium chitosan and sodium alginate are added to deionized water, mechanically stirred at 130-180°C, the speed of the stirrer is 100-200r·min-1, and poured out after stirring evenly, and placed at 60-90°C for 2-4 hours.

[0009] The beneficial effects of the present invention are: (1) The present invention uses biomimetic polymer as a binder material instead of cement, which greatly reduces the carbon emissions in the cement production process and makes a positive contribution to addressing global climate change.

[0010] (2) The bionic building materials prepared by using quaternized chitosan and sodium alginate also achieve the goal of low carbon and environmental protection. Both raw materials come from nature, and the preparation process does not require high energy consumption conditions such as high temperature and high pressure, so it has a significant energy-saving and emission reduction effect.

[0011] (3) The bionic building materials prepared by quaternized chitosan and sodium alginate also perform well in waterproofing. Since these two raw materials have good hydrophilicity and film-forming properties, the prepared materials can effectively prevent water penetration and ensure the stability and durability of the building.

[0012] (4) The present invention produces recycled concrete by crushing, screening, cleaning and grading industrial waste and construction waste to form recycled powder, fine aggregate and coarse aggregate, which partially or completely replace cement and natural sand and gravel aggregate. This recycled concrete can not only effectively utilize construction waste, but also reduce the use of natural aggregates and reduce carbon emissions. At the same time, through reasonable design, the recycled concrete can be applied to building structures to form recycled concrete structures, further expanding its scope of application.

[0013] (5) The present invention utilizes industrial waste and construction waste to prepare cement-free concrete, which is mainly reflected in high-strength bonding performance, low-carbon environmental protection, excellent anti-aging performance, good waterproof performance and recyclability. These advantages make this bionic building material have broad application prospects and huge development potential in the field of construction, and can effectively solve the problem of waste accumulation, realize the recycling of resources and sustainable development of the environment. DETAILED DESCRIPTION

[0014] The present invention will be further explained below in conjunction with specific implementation modes. It should be understood that the following specific implementation modes are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0015] The method for preparing cement-free concrete by using biomimetic polymers according to the present invention comprises the following steps: (1) Preparation of biomimetic polymer: The biomimetic polymer emulsion is a high-bonding biomimetic polymer prepared from quaternary ammonium chitosan and sodium alginate. Quaternary ammonium chitosan and sodium alginate are added to deionized water and mechanically stirred at 160°C and 180 r / min. -1 The biomimetic polymer was obtained by placing the mixture at 70°C for 3 hours.

[0016] (2) Preparation of solid waste powder: It is obtained by grinding and screening industrial waste and construction waste, such as concrete blocks, bricks, waste sand, fly ash, steel slag, blast furnace slag and other powders. The particle size range is 7-200 microns. Solid waste powder can be one type or a mixture of multiple powders.

[0017] (3) Preparation of solid waste fine aggregate: It is obtained by crushing and screening industrial waste and construction waste, such as concrete blocks, bricks, waste sand, steel slag, blast furnace slag and other fine aggregates. The particle size range is in a continuous gradation of 0.1-5 mm. Solid waste fine aggregate can be one type or a mixture of multiple fine aggregates.

[0018] (4) Preparation of coarse aggregate from solid waste: It is obtained by crushing and screening industrial waste and construction waste, such as concrete blocks, bricks, waste sand, steel slag, blast furnace slag and other coarse aggregates. The particle size range is 5-60 mm with continuous grading. The coarse aggregate from solid waste can be one type or a mixture of multiple coarse aggregates.

[0019] (5) A cement-free concrete prepared by using a bionic polymer, wherein the weight fractions of the raw materials include 290-450 parts of solid waste powder, 680-810 parts of solid waste fine aggregate, 980-1200 parts of solid waste coarse aggregate, and 160-280 parts of a bionic polymer emulsion; the weighed solid waste powder and the bionic polymer emulsion are stirred to make the materials evenly mixed to form a concrete slurry, and then solid waste fine particles and solid waste fine particles and coarse aggregate are added and stirred evenly, and the slurry is put into a mold for curing. After curing and demolding, a cement-free concrete product is formed. Example

[0020] To prepare biomimetic polymer cement-free concrete, the components are mixed in the following mass ratio: biomimetic polymer: solid waste powder with a particle size of 7-50 μm and continuous graded: solid waste fine aggregate with a particle size of 0.1-3 mm and continuous graded: solid waste coarse aggregate with a particle size of 5-15 mm and continuous graded = 160:450:680:1200, wherein the mass ratio of quaternized chitosan and sodium alginate used as raw materials for preparing the biomimetic polymer is 5:1. After the concrete is formed, it is dried and cured at a high temperature of 60° C. for 72 hours, and then demolded, which is marked as Example 1. Example

[0021] To prepare biomimetic polymer cement-free concrete, the components are mixed in the following mass ratio: biomimetic polymer: solid waste powder with a particle size of 50-150 μm and continuous graded: solid waste fine aggregate with a particle size of 0.8-4 mm and continuous graded: solid waste coarse aggregate with a particle size of 8-25 mm and continuous graded = 210:380:720:1100, wherein the mass ratio of quaternized chitosan and sodium alginate as raw materials for preparing the biomimetic polymer is 4:1. After the concrete is formed, it is dried and cured at a high temperature of 60°C for 72 hours, and then demolded, which is marked as Example 2. Example

[0022] To prepare biomimetic polymer cement-free concrete, the components are mixed in the following mass ratio: biomimetic polymer: solid waste powder with a particle size of 80-200 μm and continuous graded: solid waste fine aggregate with a particle size of 0.1-5 mm and continuous graded: solid waste coarse aggregate with a particle size of 10-30 mm and continuous graded = 240:400:750:1100, wherein the mass ratio of quaternized chitosan and sodium alginate used as raw materials for preparing the biomimetic polymer is 5:1. After the concrete is formed, it is dried and cured at a high temperature of 70°C for 72 hours, and then demolded, which is marked as Example 3. Example

[0023] To prepare biomimetic polymer cement-free concrete, the components are mixed in the following mass ratio: biomimetic polymer: solid waste powder with a particle size of 100-200 μm and continuous graded: solid waste fine aggregate with a particle size of 1-5 mm and continuous graded: solid waste coarse aggregate with a particle size of 10-25 mm and continuous graded = 280:290:810:980, wherein the mass ratio of quaternized chitosan and sodium alginate as raw materials for preparing the biomimetic polymer is 4:1. After the concrete is formed, it is dried and cured at a high temperature of 90°C for 72 hours and then demolded, which is marked as Example 4. Example

[0024] To prepare biomimetic polymer cement-free concrete, the components are mixed in the following mass ratio: biomimetic polymer: continuously graded solid waste powder with a particle size of 50-150 μm: continuously graded solid waste fine aggregate with a particle size of 1-5 mm: continuously graded solid waste coarse aggregate with a particle size of 15-45 mm = 210:380:720:1000, wherein the mass ratio of quaternized chitosan and sodium alginate as raw materials for preparing the biomimetic polymer is 4:1. After the concrete is formed, it is dried and cured at high temperature of 60°C for 72 hours, and then demolded, which is marked as Example 5. Example

[0025] To prepare biomimetic polymer cement-free concrete, the components are mixed in the following mass ratio: biomimetic polymer: solid waste powder with a particle size of 150-200 μm and continuous graded: solid waste fine aggregate with a particle size of 2.5-5 mm and continuous graded: solid waste coarse aggregate with a particle size of 20-60 mm and continuous graded = 240:400:750:1100, wherein the mass ratio of quaternized chitosan and sodium alginate used as raw materials for preparing the biomimetic polymer is 5:1. After the concrete is formed, it is dried and cured at a high temperature of 60°C for 72 hours, and then demolded, which is marked as Example 6.

[0026] To prepare ordinary concrete, the components were mixed in the following mass ratio: cement: solid waste fine aggregate with a particle size of 0.1-5 mm and continuous graded: solid waste coarse aggregate with a particle size of 5-25 mm and continuous graded: water = 375:750:1125:200, marked as Comparative Example 1.

[0027] To prepare ordinary concrete, the components were mixed in the following mass ratio: cement: river sand: basalt gravel: water = 375: 750: 1125: 200, marked as Comparative Example 2.

[0028] Test experiment 1: The compressive strength of cement-free concrete prepared using bionic polymers is shown in Table 1. As shown in Examples 1-6, the compressive strength reached above 13 MPa, while the compressive strength of concrete prepared using cement as a binder in Comparative Example 1 was slightly lower than that of cement-free concrete, at only 12 MPa. Therefore, this technology has good technical effects.

[0029] Table 1 Compressive strength,

[0030] It should be noted that the above content only illustrates the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing cement-free concrete using biomimetic polymers, characterized in that: The raw materials of the cement-free concrete include, by weight, 290-450 parts of solid waste powder, 680-810 parts of solid waste fine aggregate, 980-1200 parts of solid waste coarse aggregate, and 160-280 parts of bionic polymer emulsion.

2. The method for preparing cement-free concrete using biomimetic polymer according to claim 1, characterized in that: The following steps are involved: According to the raw material ratio, the weight fraction of the raw materials includes 290-450 parts of solid waste powder, 680-810 parts of solid waste fine aggregate, 980-1200 parts of solid waste coarse aggregate, and 160-280 parts of bionic polymer emulsion; the weighed solid waste powder is stirred with the bionic polymer emulsion to mix the materials evenly to form concrete slurry, and then the solid waste fine aggregate and solid waste coarse aggregate are added and stirred evenly, and the slurry is loaded into a mold for curing. After curing and demolding, a cement-free concrete product is formed.

3. The method for preparing cement-free concrete using biomimetic polymer according to claim 1, characterized in that: The solid waste powder includes powdered byproducts generated during industrial production and construction waste powder, and the particle size is in the range of 7-200 microns.

4. The method for preparing cement-free concrete using biomimetic polymer according to claim 1, characterized in that: The solid waste fine aggregate includes solid by-products generated in the industrial production process and aggregates generated by crushing and grinding construction waste, and the particle size is in the range of 0.1-5 mm.

5. The method for preparing cement-free concrete using biomimetic polymer according to claim 1, characterized in that: The solid waste coarse aggregate includes solid by-products generated in industrial production processes and coarse aggregate generated by crushing construction waste, and the particle size is in the range of 5-60 mm.

6. The method for preparing cement-free concrete using biomimetic polymer according to claim 1, characterized in that: The bionic polymer emulsion is a high-bonding bionic polymer prepared from quaternized chitosan and sodium alginate.

Citation Information

Cited By

  • Soil stabilizer based on bionic principle and application and application method thereof

    CN120647225A